Performance Evaluation of Solar Parabolic Collector Using Low Volume Fractions of Multi-Walled Carbon-nanotube in Synthetic Engine Oil - Talugeri, Vinayak; Nasi, Veeranna Basawannappa; Lalagi, Gururaj; Pattana, Nagaraj Basavaraj (Applied Science and Engineering Progress, 2024)
The use of nanofluids has been encouraged to advance the efficiency of solar collectors in previous investigations. In this experiment, the performance of solar parabolic collectors in Bangalore, India, was enhanced using low-volume fractions of multi-walled carbon nanotubes (MWCNT) and synthetic engine oil as the base fluid. To stabilize and optimize the thermal conductivity of the nanofluids, orthocresol was used as a surfactant and was further treated with magnetic stirring and ultrasonication. The resulting MWCNT-synthetic engine oil nanofluid was generated at three different volume fractions with a 1:1 MWCNT/ Orthocresol ratio and tested at different flow rates between 10:00 and 16:00 according to ASHRAE Standards. The maximum efficiency was achieved at 0.0317 vol% and a discharge of 7 L/min, which was 6.9% higher than that of the synthetic engine oil. This study shows that even at low-volume fractions of nanofluids, effective heat transfer can be achieved in solar parabolic collectors. These findings suggest that MWCNT-synthetic engine oil nanofluids have the potential to significantly advance the performance of solar parabolic collectors.